Klórpirifosz és a ciprodinil hatóanyagú növényvédő szerek együttes méreghatásának vizsgálata házityúk-embriókban - Szabó, Rita; Varga, Dorina; Budai, Péter; József, József; Saidon, Saidon; Buda, István; Major, László (GEORGIKON FOR AGRICULTURE, 2023)
Our study aimed to determine the individual and combined toxic effects of chlorpyrifos (480 g/l) insecticide (Pyrinex 48 EC) and cyprodinil (500 g/kg) fungicide (Chorus 50 WG) on the development of chicken embryos. The pesticides, 0.1 ml of 1% Pyrinex 48 EC and 0.125% Chorus 50 WG, were injected alone and together into the air chamber of the eggs before incubation. The chicken embryos were examined on the 19th day according to the following: embryonic mortality rate, type and rate of developmental abnormalities, and body weight. Embryonic mortality and developmental abnormalities were analysed with Fisher's exact test, body weight data with One-Way ANOVA, and Tukey and Dunnett tests. The combined use of Pyrinex 48 EC and Chorus 50 WG pesticides proved to be embryotoxic for chicken embryos. The incidence of embryonic mortality and embryonic developmental disorders increased when they were used simultaneously, and body weight of the embryos decreased. Pyrinex 48 EC and Chorus 50 WG had an additive effect on the embryonic mortality rate. Both pesticides were embryotoxic as confirmed by increased developmental abnormalities.
Keywords: chlorpyrifos; cyprodinil; chicken embryo; embryonic mortality; developmental disorder; toxic interaction